OP0128 Evaluation of Peripheral Blood Perfusion by Laser Speckle Contrast Analysis in Systemic Sclerosis Patients Treated with Aminaphtone. (15th July 2016) - Ruaro, B.; Pizzorni, C.; Trombetta, A.C.; Paolino, S.; Bernero, E.; Cutolo, M.; Sulli, A.
Abstract : Background: Both primary (PRP) and secondary Raynaud's phenomenon (SRP) are characterized by impairment of the microvascular system, with clinical symptoms related to decreased peripheral blood perfusion (1, 2). Different treatments are available to manage digital vasculopathy (3). Aminaphtone seems to downregulate endothelin-1 production in endothelial cells, and ameliorates RP symptoms (4, 5). Laser speckle contrast analysis (LASCA) is a validated technique to assess blood perfusion (2). Objectives: To evaluate short-time effects of aminaphtone treatment on blood perfusion by LASCA technique in patients affected by PRP or SRP. Methods: Thirty-five patients with active RP were enrolled during routine clinical assessment in November 2015 (26 SRP, mean age 64±17 SD years, mean RP duration 10±7 years; 9 PRP, mean age 49±21 SD years, mean RP duration 5±3 years). Aminaphtone 75 mg twice daily was administered in addiction to current treatments (patients were on stable drug regimen from at least two months, and did not modify it during follow-up). Blood perfusion was assessed in all patients by LASCA at baseline (T0), after one (T1) and four weeks (T4) of treatment, at the level of fingertips, periungual areas, dorsum and palm of hands, tip of noise, zygoma, forehead, and perioral regions. Blood perfusion was calculated as perfusion units (PU) (2). Raynaud condition score (RCS), Raynaud's attach frequency and duration were also assessed at the same times. Results: A progressive statistically significant increase of blood perfusion was observed from T0 to T4 in all skin areas (median PU at T0, T1, T4 respectively: fingertips 56, 93, 108; periungual areas 44, 81, 90; dorsum of hands 38, 64, 73; palm of hands 60, 85, 99; tip of noise 95, 114, 124; zygoma 134, 140, 150; forehead 113, 117, 130; perioral region 138, 144, 149; whole face 121, 132, 143. p<0.0001 for all areas). In particular, all patients treated with aminaphtone showed an increase of blood perfusion from T0 to T1, and 30 out of 35 patients had a further increase of blood perfusion from T1 to T4. A progressive statistically significant decrease of RCS (median at T0, T1, T4: 7, 6, 4) Raynaud frequency (median at T0, T1, T4: 2, 2, 1 attacks/day) and duration (median at T0, T1, T4: 20, 20, 10 minutes) was also observed from T0 to T4 (p<0.0001). The results were similar for both PRP and SRP. Two patients had to stop the drug due to headache. Conclusions: This study demonstrates that the therapy with aminaphtone seems to increase in short-time and maintain skin blood perfusion, as well as seems to improve RP symptoms. Larger studies might further confirm the role of aminaphtone in the treatment of RP secondary to systemic sclerosis. References: Cutolo M, et al. Nat Rev Rheumatol 2010;6, 578–87. Ruaro B, et al. Ann Rheum Dis. 2014;73:1181–5. Cutolo M, et al. Nat Rev Rheumatol 2015;11:569–71. Parisi S, et al. Am J Int Med 2015;3;204–9. Scorza R, et al. Drugs R D 2008;9:251–7. Disclosure of Interest: None declared